Contemporary Marketing or Temporary Marketing?: An Analysis of Present Day "Relationship Marketing" of Indian Organizations - Venkatesh, R. (Indian Journal of Marketing, 2013)
Customer relationship is the buzz word in marketing these days. Every organization sets its mission to treat customers as the most important stakeholders of a business. Several programmes are drawn to satisfy and delight the customers. Given the competition that exists in today’s environment, every organization comes out with novel programmes to delight the customers. All these innovative programmes, copied by the competitors in no time, lose their value within months of introduction. The contemporary relationship styles remain temporary styles for attracting and retaining customers. What is then that endears the customers to you in the long run? The present paper examines various customer-friendly programmes that companies dish out, and the reactions of the customers to these Relation building programs in the last six years. The article also examines the long-term effects of the present-day relationship marketing.